Automorphisms of the universal enveloping algebra of a finite-dimensional Zinbiel algebra with zero multiplication - Zhangazinova, D.M.; Naurazbekova, A.S. (Karagandy University of the name of acad. E.A. Buketov, 2023)
In recent years there has been a great interest in the study of Zinbiel (dual Leibniz) algebras. Let A be Zinbiel algebra over an arbitrary field K and let ei, e2, ... , em, ... be a linear basis of A. In 2010 A. Naurazbekova, using the methods of GrObner-Shirshov bases, constructed the basis of the universal (multiplicative) enveloping algebra U(A) of A. Using this result, the automorphisms of the universal enveloping algebra of a finite-dimensional Zinbiel algebra with zero multiplication are described.
Нелдік кебейтідісі бар ақырлыөлшемді Зинбил алгебрасының, универсалды ораушы алгебрасыныц автоморфизмдері
Автоморфизмы универсальной обертывающей алгебры конечномерной алгебры Зинбиля с нулевым умножением
Keywords: Zinbiel (dual Leibniz) algebra; universal (multiplicative) enveloping algebra; basis; automorphism; affine automorphism